3D PRINTING TECHNOLOGY FOR MONOLITHIC BEAMS WITH THE POSSIBILITY OF REINFORCING BARS - Demchyna, B.; Vozniuk, L.; Surmai, M.; Burak, D.; Shcherbakov, S. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The integration of 3D printing technology in construction has the potential to reduce costs and accelerate the construction and installation processes. While this technology is gaining global attention, Ukraine currently lacks regulations governing the design and construction of structures using 3D printing. Additionally, there is a limited experimental base regarding the bearing capacity and deformability of printed structures. This publication proposes a methodology for the production of monolithic beams reinforced with single bars using a construction 3D printer. It outlines the entire process of manufacturing, from the design phase to product fabrication and readiness for experimental research. To carry out the research, the design of the beams was first created using graphic software systems, which facilitated the formulation of tasks for a construction-grade 3D printer, considering the capabilities of this technology. Design and production drawings of the samples are included in this publication. The reinforced monolithic beams were printed using a construction 3D printer by the Ukrainian company 3D TECHNOLOGY UTU LLC, following the developed work algorithm. This methodology enabled the reinforcement of structures with single bars, in compliance with regulatory requirements, while allowing for future experiments. As a result of this work, reinforced monolithic beams were successfully printed using the developed technology. To assess the physical and mechanical characteristics of the materials, samples of cubes and prisms were printed and cast into formwork. Additionally, reinforcement samples were created from the same batch used to reinforce the beams. The proposed technology for producing beams with a 3D construction printer resulted in structures that adhered to previously established design solutions. The detailed sequence for printing beams allowed for effective reinforcement of monolithic beams with single bars.